2022
DOI: 10.23887/jjpgsd.v10i3.49510
|View full text |Cite
|
Sign up to set email alerts
|

Media Buku Pintar Meningkatkan Hasil Belajar Keterampilan Dasar Siswa Kelas I Sekolah Dasar

Abstract: Many students have difficulty improving basic skills. In addition, the media that can assist teachers in teaching students is also lacking, so students find it challenging to learn calistung. This study aims to develop Smart Book Media in Improving Learning Outcomes of Basic Skills for First Grade Elementary School Students. This type of research is the development of the ADDIE model. The test subjects were 2 media experts and 2 material experts. The trial subjects were 1 practitioner and 28 grade I elementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Alkhairaat Kalukubula (Mailili, 2018). Other one explained that mathematics smart bottle cap learning media can improve student learning outcomes (Zumrotun & Attalina, 2020). Supported by study that revealed that the use of bamboo dancing media can increase understanding of the concepts of multiplication and division of whole numbers (Wahyuningtyas, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Alkhairaat Kalukubula (Mailili, 2018). Other one explained that mathematics smart bottle cap learning media can improve student learning outcomes (Zumrotun & Attalina, 2020). Supported by study that revealed that the use of bamboo dancing media can increase understanding of the concepts of multiplication and division of whole numbers (Wahyuningtyas, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…According to Rosmaya (2018) Writing is the process of conveying information in the form of graphic symbols that can be read and understood by the writer himself or by others. Through writing activities, students are expected to be able to convey thoughts, dreams and feelings in the form of meaningful written symbols (Aprelia, 2019). There are several types of writing that a student must master, one of which is argumentative writing.…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous studies show that writing skills still need to improve, especially for elementary school students. Many students are good at telling stories in the learning process, but when doing writing activities, they must communicate stories in words or paragraphs (Aprelia et al, 2019;Rinawati, 2020). Although some students can convey their ideas in writing, some sentences must be more structured.…”
Section: Introductionmentioning
confidence: 99%